Why should anyone work here? what it takes to create an authentic organization - Goffee, Robert (Boston Harvard Business Review Press, 2015)
What would that company be like? How would you build and sustain it? As a leader, you need to know. In the past, businesses made people conform to the organization?s needs. But the old paradigm has shifted. Now leaders must transform their organizations so that they attract the right people, keep them, and inspire them to do their best work. How do you create a culture people want to belong to?
Keywords: BUSINESS & ECONOMICS / Workplace Culture